Comparative economic systems : models and cases - Bornstein, Morris (Homewood, Ill. : R.D. Irwin, 1965)
This book is about the organization, operation, and performance of economic systems, both in theory and in practice. It deals with alternative methods of determining the bill of goods to be produced, the allocation of resources to produce it, and the distribution of the resulting income.
Includes bibliographical references.
rpm 02/11/2017
Loans
Keywords: Comparative economics